Pathogens in ornamental waters: a pilot study - Nascimento, Maria (2016)
In parks, ornamental waters of easy access and populated with animals are quite attractive to children and yet might hide threats to human health. The present work focuses on the microbiota of the ornamental waters of a Lisboa park, characterized during 2015. The results show a dynamic microbiota integrating human pathogens such as Klebsiella pneumoniae, Aeromonas spp. and Enterobacter spp., and also antibiotic resistant bacteria. K. pneumoniae and Aeromonas spp. were present as planktonic and biofilm organized bacteria. In vitro K. pneumoniae and Aeromonas spp. showed an enhanced ability to assemble biofilm at 25 C than at 37 C. Bacteria recovered from biofilm samples showed an increased antibiotic resistance compared to the respective planktonic counterparts.